Geometry Learning Design for Facilitate Pancasila Student Profile Critical Reasoning Dimensions of Elementary School Students - Bagus Ardi Saputro; Hana Tsania Maurizka; Veryliana Purnamasari (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
The background of the problem in this research is the lack of developing reasoning abilities in studying geometry material so that student have difficulty accepting geometric concepts in flat shape material, especially those related to sides, lines, spaces, angles, and symbols. The purpose of this study was to analyze students’ critical reasoning abilities inn using the geometry learning design and to describe the effevctiveness of using the geometry learning design that facilitates the students’ profiles of Pancasila dimensions of critical reasoning. This study uses Didactial Design Research (DDR). The existence of this geometry learning design is very helpful for fostering students’ critical reasoning abilities simply through triggering questions that are made to form geometric concepts independently based on their reasoning, learning activities that involve students increase student enthusiasm, besides that, GeoGebra media is a means to students in understanding the geometry of interesting flat shapes. It can be concluded that the use of geometry learning design to facilitate the profile of Pancasila students on the dimension of critical reasoning is effective in learning.